19. Histological of Thymus in Tegal Duck (Anas javanicus) at Different Ages - Hamdani Budiman; Anugrah Septian; Hamny Hamny; Zainuddin Zainuddin; Cut Dahlia Iskandar; Mustafa Sabri; Muhammad Hambal; Abdul Harris (Jurnal Medika Veterinaria, 2019)
The aim of this research was to observe the histological of the thymus in tegal duck (Anas javanicus) according to the variation of ages. The animals used in this research were one month, two months and three months old of tegal duck. The thymus of each duck was analyzed by Hematoxylin-Eosin (HE) method and then observed under a light microscope. The result of the research performed differences in thymus structure of these three ages. The cortex had increased at the age of 2 months and decreased at the age of 3 months. The longest diameter of medulla at the age of 3 months was followed by ages 2 months and 1 month of tegal ducks.  The distribution of Hassall's body had increased at every age level. So, the cortex thickness decreased at the age of 2 months to 3 months, while the diameter of the medulla was getting longer.